The Impact of Yemen's Proxy War on Geopolitics in the Middle East 2015-2023 - Susilowati, Ida; Nur Rizqita, Sheilavia; Candra, Rudi (Prodi Hubungan Internasional Program Magister Univ. Muhammadiyah Yogyakarta, 2025)
Yemen's strategic position in the region has led to the escalation of its internal conflict into a proxy war between Saudi Arabia and Iran. This study aims to analyze the impact of Yemen's proxy war on Middle East geopolitics from 2015 to 2023, employing a qualitative descriptive content analysis with a regional geopolitical approach, informed by literature study techniques in data collection. The results showed that the proxy war in Yemen has impacted Middle Eastern geopolitics, particularly in the security and economic sectors. Iran's support for the Houthis militia has prompted responses from other regional countries based on their respective interests. The intensity of Houthi attacks on Yemen's border areas has also created border insecurity and increased tensions between countries in the region. Meanwhile, in the economic and trade sectors, the proxy war in Yemen has resulted in increased operational tariffs on regional trade, forcing countries to adjust their economic policies. This study reinforces the notion that a country's geographic position influences the geopolitics of the surrounding region and has the potential to create a domino effect on regional political instability, as seen in the conflict in Yemen.